Optimization of processing conditions in drying of different parts pumpkin powder using air fryer method - Nik Murzaini, Nik Masturah; Taip, Farah Saleena (Faculty of Engineering, Universiti Putra Malaysia, 2016)
This work focused on optimization of drying process during the production of different parts of pumpkin powder. Different parts such as, pumpkin flesh, skin, and unpeeled pumpkin were dried using air fryer. The flesh, unpeeled flesh and pumpkin skin were cut at measurement ( 2 cm x 1 cm) and pretreated with limewater treatment prior to drying. The samples immersed in limewater at 27ºC for about 25 minutes. The samples were dried at 80º C 90 ºC and 100 ºC with time 165 minutes, 142.50 minutes and 120 minutes. For optimization, result shown the best temperature of air fryer about 80ºC and the time for experiment occur approximately 2 H 45 minutes. Firstly, for pumpkin peeled and unpeeled powders, the temperature also time are minimize approximately 80 ͦC and 120 minutes. Besides, the moisture content of powder was targetted about 5%. Secondly, the desirability criteria for skin powder was minimize temperature 80 ͦC, maximize 165 minutes of time and moisture content targetted 5%. This is because, to maintain the beta coretene in pumpkin samples, the temperature of drying method should not more than 80 ºC. Lastly, moisture content in powder must not more than 10% to get the good quality of pumpkin powder.